The defense of the Amazon and its militarization - Penido, Ana Penido [UNESP]; Mathias, Suzeley Kalil [UNESP]; Barbosa, Lisa Sousa [UNESP] (Univ Federal Para, 2022)
The dispute for control over the Amazon's resources is intense, particularly as hegemonic competition on a global scale intensifies. In general, military sectors predominate in the discussion about what threatens this territory. This paper aims to critically discuss military thinking about the region, organized around five assumptions: sovereignty; geopolitics; the self-perception that only the military is committed to the defense of the Amazon; the vision that the Amazon should be integrated into the country; and a focus on borders, which fuels distrust of neighbors. Based on a bibliographical survey and elements of situational analysis, a tendency towards militarization of the formulations about the Amazonian reality is identified, with various reflections. The text is collated with suggestive comments for a new regional defense policy, based on other assumptions.
Keywords: Amazon; Militarization; Military thinking; Brazil